Pengaruh Brand Awareness Terhadap Minat Beli Cokelat Silverqueen pada Konsumen Minimarket di Berbagai Wilayah Tangerang - Ade Miko Putra Gunanda; Kharisma Alifiyah Rahmawati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the influence of Brand Awareness on the Purchase Intention of consumers of SilverQueen chocolate products in the Tangerang area. The method used in this study is a quantitative approach with survey techniques, involving 100 respondents from various demographic backgrounds. Data collection was conducted through questionnaires using a Likert scale and analyzed with SPSS software. The results of the validity test show that all indicators used to measure Brand Awareness and Purchase Intention are valid, with the calculated r value exceeding the table r value and significance below 0.05. The reliability test shows a Cronbach's Alpha value of 0.936, indicating that the questionnaire has very good consistency. The normality, multicollinearity, and heteroscedasticity tests indicate that the regression model meets the classical assumptions. The results of the coefficient of determination (R²) analysis indicate that Brand Awareness contributes 11.9% to Purchase Intention. The t-test shows that Brand Awareness has a significant positive effect on Purchase Intention, with a calculated t value of 3.630, greater than the t-table value, and a significance value of 0.000, which is less than 0.05. These findings confirm that the higher the level of Brand Awareness, the greater the likelihood that consumers will purchase SilverQueen products. This research provides valuable insights for the company in designing effective marketing strategies, emphasizing the importance of increasing Brand Awareness to boost consumer purchase interest.